Method for regenerating acid gas adsorption device and method for manufacturing acid gas adsorption device
By crushing and regenerating the materials of the acid gas adsorption device to form a new acid gas adsorption layer, the problem of reduced CO2 recovery rate during repeated use of the existing device is solved, and the effects of cost reduction and device life extension are achieved.
Patent Information
- Application Number
- CN202380039969.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-11-30
- Filing Date
- 2023-06-19
- Publication Date
- 2025-01-24
AI Technical Summary
During the repeated use of existing acid gas adsorption devices, the CO2 recovery rate will gradually decrease due to the repetition of impurities and heating treatment, resulting in increased operating costs and requiring replacement of the devices.
By crushing the useful acidic gas adsorption device, the renewable material powder is obtained, and new substrates are formed to form a new acidic gas adsorption layer containing acidic gas adsorption materials to achieve the regeneration of the device.
This method can significantly reduce the operating cost of acidic gas adsorption device, extend the service life of the device, and increase the recycling rate of CO2.
Smart Images

Figure CN119365249A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a regeneration method of an acid gas adsorption device and a manufacturing method of the acid gas adsorption device. Background Art
[0002] In recent years, efforts have been made to separate and recover acid gases contained in the atmosphere in order to reduce the environmental load. As such acid gases, carbon dioxide (hereinafter sometimes referred to as CO2) that causes global warming can be mainly cited. As a representative example of this effort, the carbon dioxide capture, utilization and storage (CCUS) cycle is known. As a carbon dioxide adsorption device for separating and recovering carbon dioxide, a CO2 capture absorbent structure has been proposed, which includes: a honeycomb substrate having a plurality of partitions, thereby forming a plurality of flow channels; and a functional structural unit, which is arranged in and on the partitions (for example, see Patent Document 1). In the CO2 capture absorbent structure, CO2 can be captured from a gas fluid flowing in the absorbent structure, and the captured CO2 can be released under specified conditions. However, if the CO2 capture absorbent structure described in Patent Document 1 is used to repeatedly adsorb and release CO2 contained in the atmosphere, the CO2 recovery rate may gradually decrease due to impurities contained in the atmosphere and repeated heating treatment. In this case, the entire CO 2 capturing absorbent structure needs to be replaced, which causes a problem of increased running costs.
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: International Publication No. 2013 / 119929 Summary of the invention
[0006] The main object of the present invention is to provide a method for regenerating an acid gas adsorption device and a method for manufacturing an acid gas adsorption device that can reduce running costs.
[0007] [1] A method for regenerating an acid gas adsorption device according to an embodiment of the present invention comprises the following steps: supplying acid gas to the acid gas adsorption device in a manner that the acid gas adsorption layer of the acid gas adsorption device having a substrate and an acid gas adsorption layer is in contact with the acid gas adsorption layer, so that the acid gas is adsorbed on an acid gas adsorption material contained in the acid gas adsorption layer, wherein the acid gas adsorption layer is arranged on the surface of the substrate; desorbing the acid gas from the acid gas adsorption material; pulverizing the acid gas adsorption device that has undergone the steps of adsorbing the acid gas and desorbing the acid gas to obtain a regenerated material powder; and molding the regenerated material powder to obtain a substrate, and forming an acid gas adsorption layer containing the acid gas adsorption material on the surface of the substrate.
[0008] [2] In the method for regenerating an acid gas adsorption device described in [1] above, the acid gas may be carbon dioxide.
[0009] [3] In the method for regenerating an acid gas adsorption device described in [1] or [2] above, the substrate may be a honeycomb substrate having partitions defining a plurality of cells, and the acid gas adsorption layer may be formed on surfaces of the partitions.
[0010] [4] In the method for regenerating an acidic gas adsorption device described in any one of [1] to [3] above, the material constituting the above-mentioned substrate is selected from cordierite, alumina, mullite, silicon carbide, silicon-silicon carbide composite materials, silicon nitride or a combination thereof.
[0011] [5] In the regeneration method of the acid gas adsorption device described in any one of [1] to [4] above, the acid gas adsorption material is selected from nitrogen-containing compounds, organic metal structures, activated carbon, nitrogen-doped carbon, alkaline compounds, carbonates, bicarbonates, zeolites, ionic liquids or combinations thereof.
[0012] [6] In the method for regenerating an acidic gas adsorption device according to any one of [1] to [5] above, the acidic gas adsorption layer may further include a porous carrier.
[0013] [7] In the method for regenerating an acidic gas adsorbent device according to any one of [1] to [6] above, the acidic gas adsorbent layer may include particles containing at least the acidic gas adsorbent material and an organic binder capable of binding the particles. The organic binder may be soluble in an aprotic polar solvent and substantially insoluble in a protic polar solvent.
[0014] [8] The method for regenerating the acidic gas adsorbent device described in [7] above may further include the following steps: bringing an aprotic polar solvent into contact with the recycled material powder containing the organic binder to dissolve the organic binder in the aprotic polar solvent; and adding a protic polar solvent to the organic binder solution obtained by dissolving the organic binder in the aprotic polar solvent to precipitate the organic binder and recover the organic binder. In this case, an acidic gas adsorbent layer containing the recovered organic binder and particles containing at least the acidic gas adsorbent can be formed on the surface of the substrate obtained by molding the recycled material powder.
[0015] [9] Another aspect of the present invention relates to a method for manufacturing an acid gas adsorption device, which includes the following steps: supplying acid gas to the acid gas adsorption device in a manner that the acid gas adsorption layer of the acid gas adsorption device is in contact with a substrate and an acid gas adsorption layer, so that the acid gas is adsorbed on an acid gas adsorption material included in the acid gas adsorption layer, wherein the acid gas adsorption layer is arranged on the surface of the substrate; allowing the acid gas to be separated from the acid gas adsorption material; pulverizing the acid gas adsorption device that has undergone the steps of adsorbing the acid gas and separating the acid gas to obtain a regenerated material powder; and molding the regenerated material powder to obtain a substrate, and forming an acid gas adsorption layer including the acid gas adsorption material on the surface of the substrate.
[0016] Effects of the Invention
[0017] According to the embodiments of the present invention, a method for regenerating an acid gas adsorption device and a method for manufacturing an acid gas adsorption device that can reduce running costs can be realized. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is a schematic perspective view of a carbon dioxide adsorption device according to one embodiment of the present invention.
[0019] Figure 2 yes Figure 1 A schematic cross-sectional view of a carbon dioxide adsorption device.
[0020] Figure 3 It is by Figure 1 A schematic three-dimensional diagram of a regenerated base material formed by molding the regenerated material powder obtained by crushing the carbon dioxide adsorption device. DETAILED DESCRIPTION
[0021] Hereinafter, embodiments of the present invention will be described with reference to the drawings; however, the present invention is not limited to these embodiments.
[0022] A. Overview of the regeneration method of the acid gas adsorption device
[0023] Figure 1 This is a schematic perspective view of a carbon dioxide adsorption device according to one embodiment of the present invention. Figure 2 yes Figure 1 A schematic cross-sectional view of a carbon dioxide adsorption device, Figure 3 It is by Figure 1 A schematic three-dimensional diagram of a regenerated base material formed by molding the regenerated material powder obtained by crushing the carbon dioxide adsorption device.
[0024] A method for regenerating an acid gas adsorption device according to one embodiment of the present invention includes the following steps: supplying acid gas to an acid gas adsorption device 100 in a manner that contacts an acid gas adsorption layer 15, so that the acid gas is adsorbed on the acid gas adsorption material, the acid gas adsorption device 100 including a substrate 1 and an acid gas adsorption layer 15, the acid gas adsorption layer 15 being arranged on the surface of the substrate 1 and containing the acid gas adsorption material (adsorption step); desorbing the acid gas from the acid gas adsorption material (desorption step); pulverizing the acid gas adsorption device 100 subjected to the adsorption step and the desorption step to obtain a regenerated material powder (pulverization step); and molding the regenerated material powder to obtain a substrate 1, and forming an acid gas adsorption layer 15 containing the acid gas adsorbent on the surface of the substrate 1 (re-formation step).
[0025] The inventors of the present invention have found that the material powder obtained by crushing the acid gas adsorption device that has been subjected to the adsorption process and the desorption process can be directly reused as the raw material of the substrate, and thus the present invention has been completed. More specifically, the acid gas adsorption device that has been subjected to the adsorption process and the desorption process is crushed to obtain a regenerated material powder, and the regenerated material powder is molded to obtain a substrate, and an acid gas adsorption layer is formed on the surface of the substrate. As a result, the acid gas adsorption device can be regenerated (manufactured) at a lower cost than when the substrate is made from new raw materials. Therefore, even if the acid gas adsorption device is repeatedly replaced and the adsorption and desorption of acid gas are performed for a long time, the running cost can be significantly reduced.
[0026] Examples of the acidic gas include carbon dioxide (CO 2 ), hydrogen sulfide, sulfur dioxide, nitrogen dioxide, and hydrogen chloride.
[0027] In one embodiment, the acidic gas is carbon dioxide (CO2). In this embodiment, the acidic gas adsorption device 100 is a carbon dioxide adsorption device 100, the acidic gas adsorption layer 15 is a carbon dioxide adsorption layer 15, and the acidic gas adsorption material is a carbon dioxide adsorption material. Hereinafter, the carbon dioxide adsorption device 100 as one embodiment of the acidic gas adsorption device will be described in detail.
[0028] B. Carbon dioxide adsorption device
[0029] As described above, the carbon dioxide adsorption device 100 includes a substrate 1 and a carbon dioxide adsorption layer 15. The structure of the substrate 1 is not particularly limited, and examples thereof include: a filter structure such as a honeycomb or a filter cloth; a particle structure, etc. The carbon dioxide adsorption layer 15 is not particularly limited as long as it is disposed on the surface of the substrate 1.
[0030] B-1. Base material (honeycomb base material)
[0031] In one embodiment, the substrate 1 is a honeycomb substrate 10 having a plurality of cells 14 .
[0032] The cells 14 extend from the first end face 1a (inflow end face) to the second end face 1b (outflow end face) of the honeycomb substrate 10 in the longitudinal direction (axial direction) of the honeycomb substrate 10 (see Figure 2 ). The cell 14 has any appropriate shape in the cross section of the honeycomb substrate 10 in a direction perpendicular to the longitudinal direction. Examples of the cross-sectional shape of the cell include: a triangle, a quadrilateral, a pentagon, a polygon larger than a hexagon, a circle, and an ellipse. The cross-sectional shape and size of the cell may be all the same, or at least part of them may be different. Among the cross-sectional shapes of such cells, preferably, a hexagon or a quadrilateral may be mentioned, and more preferably, a square, a rectangle or a hexagon may be mentioned.
[0033] The cell density in the cross section of the honeycomb substrate in a direction perpendicular to the longitudinal direction (i.e., the number of cells 14 per unit area) can be appropriately set according to the purpose. The cell density can be, for example, 4 cells / cm 2 ~320 compartments / cm 2 When the cell density is within such a range, the strength and effective GSA (geometric surface area) of the honeycomb substrate can be sufficiently ensured.
[0034] The honeycomb substrate 10 has any appropriate shape (overall shape). Examples of the shape of the honeycomb substrate include a cylindrical shape with a circular bottom, an elliptical cylindrical shape with an elliptical bottom, a prism shape with a polygonal bottom, and a column shape with an irregular bottom. The honeycomb substrate 10 shown in the figure has a cylindrical shape. The outer diameter and length of the honeycomb substrate can be appropriately set according to the purpose. Although not shown in the figure, the honeycomb substrate may have a hollow area in the center of the cross section in a direction perpendicular to the longitudinal direction.
[0035] Typically, the honeycomb substrate 10 includes an outer peripheral wall 11 and partition walls 13 located inside the outer peripheral wall 11. In the example shown in the figure, the outer peripheral wall 11 and the partition walls 13 are formed integrally. The outer peripheral wall 11 and the partition walls 13 may be separate bodies.
[0036] The outer peripheral wall 11 has a cylindrical shape. The thickness of the outer peripheral wall 11 can be set arbitrarily and appropriately. The thickness of the outer peripheral wall 11 is, for example, 0.1 mm to 10 mm.
[0037] The partition wall 13 defines a plurality of compartments 14. More specifically, the partition wall 13 includes a first partition wall 13a and a second partition wall 13b, which are orthogonal to each other, and the first partition wall 13a and the second partition wall 13b define a plurality of compartments 14. The cross-sectional shape of the compartment 14 is a quadrilateral except for the portion where the first partition wall 13a and the second partition wall 13b contact the outer peripheral wall 11. It should be noted that the configuration of the partition wall is not limited to the above-mentioned partition wall 13. The partition wall may include: a first partition wall extending in a radial direction, and a second partition wall extending in a circumferential direction, which define a plurality of compartments.
[0038] The thickness of the partition wall 13 can be appropriately set according to the purpose of the honeycomb substrate. Typically, the thickness of the partition wall 13 is thinner than the thickness of the peripheral wall 11. The thickness of the partition wall 13 is, for example, 0.03 mm to 0.6 mm. For example, the thickness of the partition wall is measured by cross-sectional observation using a SEM (scanning electron microscope). If the thickness of the partition wall is within such a range, the mechanical strength of the honeycomb substrate can be sufficient, and the opening area (the total area of the cells in the cross section) can be sufficient.
[0039] The porosity of the partition wall 13 can be appropriately set according to the purpose. The porosity of the partition wall 13 is, for example, 15% or more, preferably 20% or more, and is, for example, 70% or less, preferably 45% or less. The porosity can be measured, for example, by mercury penetration.
[0040] The density of the partition walls 13 can be appropriately set according to the purpose. For example, the density of the partition walls 13 is 1.7 g / cm 3 Above, preferably 1.8 g / cm 3 Above, and for example 2.6 g / cm 3 Below, preferably 2.8 g / cm 3 It should be noted that, for example, the density can be measured by mercury intrusion porosimetry.
[0041] As a material constituting the partition wall 13, ceramics can be cited representatively. As ceramics, for example, silicon carbide, silicon-silicon carbide composite materials, cordierite, mullite, alumina, silicon nitride, spinel, silicon carbide-cordierite composite materials, lithium aluminum silicate and aluminum titanate can be cited. The materials constituting the partition wall can be used alone or in combination. Among the materials constituting the partition wall, preferably, cordierite, alumina, mullite, silicon carbide, silicon-silicon carbide composite materials and silicon nitride can be cited, and more preferably, silicon carbide and silicon-silicon carbide composite materials can be cited.
[0042] Typically, the honeycomb substrate 10 is produced by the following method. First, a binder and water or an organic solvent are added to the material powder containing the ceramic powder as required, and the obtained mixture is kneaded to form a blank, which is then formed into a desired shape, dried, and fired as required to produce the honeycomb substrate 10. It should be noted that the method for producing the honeycomb substrate is described in detail in the description of the reforming step in the item E.
[0043] B-2. Carbon dioxide adsorption layer
[0044] In one embodiment, the carbon dioxide adsorption layer 15 is formed on the surface of the partition wall 13. In the honeycomb substrate 10, a gas flow path 16 is formed in a portion (representatively, a central portion) of the cross section of the cell 14 where the carbon dioxide adsorption layer 15 is not formed. The carbon dioxide adsorption layer 15 may be formed on the entire inner surface of the partition wall 13 (i.e., surrounding the gas flow path 16) as shown in the example shown in the figure, or may be formed on a portion of the surface of the partition wall. If the carbon dioxide adsorption layer 15 is formed on the entire inner surface of the partition wall 13, the removal efficiency of CO2 can be improved.
[0045] The gas flow path 16 extends from the first end face 1a (inflow end face) to the second end face 1b (outflow end face) in the same manner as the compartment 14. The cross-sectional shape of the gas flow path 16 may be the same as that of the compartment 14, preferably a hexagon or a quadrilateral, more preferably a square, a rectangle or a hexagon. The cross-sectional shape and size of the gas flow path 16 may be the same in all or may be at least partially different.
[0046] The thickness of the carbon dioxide adsorption layer 15 is not particularly limited, and is, for example, 10 μm or more, preferably 50 μm or more, and, for example, 1000 μm or less, preferably 500 μm or less.
[0047] B-2-1. Carbon dioxide adsorption layer formed by carbon dioxide adsorption material
[0048] The carbon dioxide adsorbing layer 15 contains a carbon dioxide adsorbing material as an example of an acidic gas adsorbing material. In one embodiment, the carbon dioxide adsorbing layer is formed of the carbon dioxide adsorbing material and is directly supported on the partition wall so as to face the gas flow path.
[0049] As the carbon dioxide adsorbent, any appropriate compound that can adsorb and desorb CO2 can be used. Examples of carbon dioxide adsorbents include: nitrogen-containing compounds described below; alkaline compounds such as sodium hydroxide and potassium hydroxide; carbonates such as calcium carbonate and potassium carbonate; bicarbonates such as calcium hydrogen carbonate and potassium hydrogen carbonate; organometallic structures (MOFs) such as MOF-74, MOF-200, and MOF-210; zeolites; activated carbon; nitrogen-doped carbon; ionic liquids, etc.
[0050] Among the carbon dioxide adsorbents, nitrogen-containing compounds are more preferably cited. More specifically, nitrogen-containing compounds include: amine compounds such as monoethanolamine, diethanolamine, triethanolamine, N-(3-aminopropyl)diethanolamine, aminopropyltrimethoxysilane, polyethyleneamine, methyldiethylamine, and tetraethylenepentamine; piperazine compounds such as 1-(2-hydroxyethyl)piperazine; aminosilane coupling agents such as polyethyleneiminetrimethoxysilane, aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, and N-(2-aminoethyl)-3-aminopropyltrimethoxysilane; organic polymers having primary to tertiary amino groups such as polyethyleneimine, polyamideamine, and polystyrene endowed with amino groups; organic monomers having primary to tertiary amino groups such as ethyleneimine and styrene endowed with amino groups; and organic / inorganic compounds endowed with amino groups as substituents. The carbon dioxide adsorbents can be used alone or in combination.
[0051] In this embodiment, the carbon dioxide adsorption layer does not substantially contain any component other than the carbon dioxide adsorption material. When the carbon dioxide adsorption layer is formed of the carbon dioxide adsorption material, the content of the carbon dioxide adsorption material in the carbon dioxide adsorption layer is typically 95.0 mass % or more and 100 mass % or less. If the content of the carbon dioxide adsorption material is within the above range, an excellent CO2 recovery rate can be stably ensured.
[0052] The carbon dioxide adsorption layer may contain an ionic liquid. In this case, the carbon dioxide adsorption layer preferably contains an ionic liquid and a carbon dioxide adsorbent material other than the ionic liquid (hereinafter referred to as other carbon dioxide adsorbent material). Typically, the ionic liquid is coated with other carbon dioxide adsorbent materials (e.g., nitrogen-containing compounds). Therefore, it is possible to achieve improved performance and longer life of the carbon dioxide adsorbent material.
[0053] Ionic liquids are liquid "salts" composed only of ions (anions and cations), and are in a liquid state at normal temperature and pressure (23°C, 0.1 MPa). Examples of cations of ionic liquids include: ammonium ions such as imidazolium salts and pyridinium salts, phosphonium ions, sulfonium salts, inorganic ions, and the like. Examples of anions of ionic liquids include: halogen ions such as bromide ions and trifluoromethanesulfonates; boron ions such as tetraphenylborate; phosphorus ions such as hexafluorophosphate; sulfur ions such as alkyl sulfonates. The above ionic liquids can be used alone or in combination. Among the ionic liquids, preferably, a combination of imidazolium salts as cations and trifluoromethanesulfonates as anions can be mentioned.
[0054] The content ratio of the ionic liquid is, for example, 0.000001 parts by mass or more, preferably 0.00001 parts by mass or more, and is, for example, 0.1 parts by mass or less, preferably 0.05 parts by mass or less, relative to 1 part by mass of other carbon dioxide adsorbents. If the content ratio of the ionic liquid is within the above range, the performance improvement and long life of the carbon dioxide adsorbent can be stably achieved.
[0055] B-2-2. Carbon dioxide adsorption layer including carbon dioxide adsorbent and porous body
[0056] In one embodiment, the carbon dioxide adsorption layer includes a porous carrier in addition to the above-mentioned carbon dioxide adsorption material. In this case, the carbon dioxide adsorption material is typically supported on the porous carrier and faces the gas flow path. If the carbon dioxide adsorption layer includes a porous carrier, the carbon dioxide adsorption material can be suppressed from falling off from the carbon dioxide adsorption layer in the adsorption process and / or the desorption process.
[0057] The porous carrier can form mesopores in the carbon dioxide adsorption layer. As the porous carrier, for example, there can be mentioned: organometallic structures (MOFs) such as MOF-74, MOF-200, and MOF-210; activated carbon; nitrogen-doped carbon; mesoporous silica; mesoporous alumina; zeolite; carbon nanotubes, preferably, there can be mentioned: organometallic structures (MOFs), activated carbon, zeolite, mesoporous silica, and mesoporous alumina. The porous carrier can be used alone or in combination. The porous carrier preferably uses a material different from the carbon dioxide adsorption material.
[0058] The BET specific surface area of the porous carrier is, for example, 50 m 2 / g or more, preferably 500m 2 If the surface area of the porous carrier is greater than the above lower limit, the carbon dioxide adsorbent can be stably supported, thereby improving the CO2 recovery rate. The upper limit of the BET specific surface area of the porous carrier is typically 2000 m 2 / g or less.
[0059] When the carbon dioxide adsorption layer contains a carbon dioxide adsorbent and a porous carrier, the total content ratio of the carbon dioxide adsorbent and the porous carrier in the carbon dioxide adsorption layer is, for example, 30 mass% or more, preferably 50 mass% or more, and is, for example, 100 mass% or less, preferably 99 mass% or less.
[0060] In the present embodiment, the content ratio of the carbon dioxide adsorbent in the carbon dioxide adsorption layer is, for example, 30% by mass or more, preferably 50% by mass or more, and, for example, 99% by mass or less. The content ratio of the porous carrier in the carbon dioxide adsorption layer is, for example, 0.1% by mass or more, preferably 10% by mass or more, and, for example, 70% by mass or less, preferably 50% by mass or less. In addition, with respect to the content ratio of the porous carrier, relative to 1 part by mass of the carbon dioxide adsorbent, it is, for example, 0.01 parts by mass or more, preferably 0.3 parts by mass or more, and, for example, 0.7 parts by mass or less, preferably 0.5 parts by mass or less. If the content ratio of the porous carrier is within the above range, the carbon dioxide adsorbent can be more stably supported.
[0061] Typically, these carbon dioxide adsorption layers are made using the following method. The carbon dioxide adsorption material is dissolved in a solvent to prepare a solution of the carbon dioxide adsorption material. In addition, the porous carrier is added to the solvent as needed. There is no particular restriction on the order of adding the carbon dioxide adsorption material and the porous carrier. Afterwards, the solution of the carbon dioxide adsorption material is applied to a substrate (specifically, a partition), and then the coating is dried and sintered as needed to form a carbon dioxide adsorption layer.
[0062] Alternatively, a dispersion containing a carbon dioxide adsorbent other than an ionic liquid and a porous carrier is applied to a substrate, the coating is dried and sintered as necessary, and then only the ionic liquid is applied to the substrate to form a carbon dioxide adsorbing layer.
[0063] The method for preparing a carbon dioxide adsorption layer comprising a carbon dioxide adsorbent and a porous carrier is not limited to the above method. For example, the above porous carrier is dispersed in a dispersion medium to prepare a dispersion of the porous carrier, the dispersion is applied to a substrate, and then the coating is dried and sintered to form a carrier-containing film. Afterwards, a liquid carbon dioxide adsorbent or a solution of a carbon dioxide adsorbent is applied to the carrier-containing film at normal temperature and pressure. Thus, the carbon dioxide adsorbent infiltrates and is carried on the porous carrier containing the carrier film to form a carbon dioxide adsorption layer.
[0064] The method for forming the carbon dioxide adsorption layer will be described in detail in the description of the reforming step in the item E.
[0065] B-2-3. Carbon dioxide adsorption layer comprising carbon dioxide adsorbing particles and an organic binder
[0066] In another embodiment, the carbon dioxide adsorption layer includes: particles containing at least the above-mentioned carbon dioxide adsorption material, and an organic binder. The particles containing the above-mentioned carbon dioxide adsorption material have carbon dioxide adsorption capacity, and are hereinafter referred to as particles with carbon dioxide adsorption capacity. The organic binder can bond the particles with carbon dioxide adsorption capacity, and typically, fix and bond them to a substrate. The organic binder can be dissolved in non-protic polar solvents and is substantially insoluble in protic polar solvents. That is, the organic binder has tolerance (water resistance) to water as a protic polar solvent. Since the organic binder is substantially insoluble in protic polar solvents and has water resistance, it is possible to suppress the organic binder from swelling due to, for example, water vapor in the atmosphere. Therefore, the volume expansion and / or strength reduction of the organic binder can be suppressed, and further, the change in the structure maintained by the organic binder bonding the particles with carbon dioxide adsorption capacity can be suppressed. As a result, regardless of the use environment, an excellent carbon dioxide adsorption capacity can be maintained.
[0067] The surface of the carbon dioxide adsorption layer on the opposite side to the substrate preferably has a three-dimensional mesh structure or a porous layer structure. Therefore, acidic gases such as carbon dioxide can be efficiently diffused from the surface of the carbon dioxide adsorption layer toward the inside. In particular, since the organic binder has water resistance, such a fine structure can be stably maintained on the surface that can contact with acidic gases regardless of the use environment.
[0068] Typically, the carbon dioxide adsorbing particles are in a solid state at normal temperature and pressure (23°C, 0.1 MPa). The carbon dioxide adsorbing layer includes a plurality of carbon dioxide adsorbing particles. The carbon dioxide adsorbing particles contained in the carbon dioxide adsorbing layer may be primary particles or secondary particles formed by agglomeration of a plurality of primary particles.
[0069] In one embodiment, the carbon dioxide adsorbing particle includes: the carbon dioxide adsorbing material and a carrier that supports the carbon dioxide adsorbing material. However, the carbon dioxide adsorbing particle may be composed only of the carbon dioxide adsorbing material without containing a carrier. That is, the acidic gas adsorbing particle may be composed only of the carbon dioxide adsorbing material that is solid at normal temperature and pressure.
[0070] The carbon dioxide adsorbing material contained in the carbon dioxide adsorbing particles preferably includes the nitrogen-containing compounds mentioned above, and more preferably includes the organic monomers having primary to tertiary amino groups and the organic polymers having primary to tertiary amino groups. The weight average molecular weight M of the organic polymer is wThe molecular weight (in terms of polystyrene) is, for example, 1,000 or more, preferably 50,000 or more, and is, for example, 1,000,000 or less, preferably 300,000 or less.
[0071] In one embodiment, the carbon dioxide adsorbing material contained in the carbon dioxide adsorbing particles is substantially insoluble in a protic polar solvent (typically water) and an aprotic polar solvent.
[0072] The solubility of the carbon dioxide adsorbent in water is, for example, 0.1 g / 100 g-H2O or less, preferably 0.05 g / 100 g-H2O or less. If the solubility of the carbon dioxide adsorbent in water is below the above upper limit, excellent water resistance can be stably imparted to the carbon dioxide adsorption device. It should be noted that the lower limit of the solubility of the carbon dioxide adsorbent in water is typically 0.01 g / 100 g-H2O or more.
[0073] The solubility of the carbon dioxide adsorbent in the aprotic polar solvent is, for example, 1 g / 100 g-aprotic polar solvent or less, preferably 0.5 g / 100 g-aprotic polar solvent or less. If the solubility of the carbon dioxide adsorbent in the aprotic polar solvent is below the upper limit, the carbon dioxide adsorbent can be suppressed from dissolving in the aprotic polar solvent during the manufacture of the carbon dioxide adsorption device. It should be noted that the lower limit of the solubility of the carbon dioxide adsorbent in the aprotic polar solvent is typically 0.01 g / 100 g-aprotic polar solvent or more.
[0074] The solubility parameter of the carbon dioxide adsorbent is, for example, 7 or more, preferably 8 or more, and is, for example, 20 or less, preferably 15 or less. For example, the solubility parameter can be calculated by the Hildebrand method.
[0075] As the carrier, any suitable carrier that can support the carbon dioxide adsorbent can be used. The carrier is preferably the above-mentioned porous carrier. In addition, from the viewpoint of thermal conductivity, a metal material is sometimes used. For example, steel materials such as carbon steel and alloy steel; non-ferrous metals such as copper, aluminum, nickel, and their alloys can be cited. In the case of a metal material, it is not limited to a porous shape.
[0076] As an organic binder, any appropriate organic compound that can bind particles with carbon dioxide adsorption capacity can be used. The organic binder can be dissolved in aprotic polar solvents and is substantially insoluble in protic polar solvents. As an organic binder, for example, fluoropolymers such as polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), perfluoroalkoxyalkane (PFA), perfluoroethylene propylene copolymer (FEP), ethylene tetrafluoroethylene copolymer (ETFE); amorphous plastics such as polyethersulfone (PES). The organic binder can be used alone or in combination.
[0077] Among the organic binders, preferably, an organic binder having at least water as a poor solvent (an organic binder substantially insoluble in water) can be cited, more preferably, a fluoropolymer can be cited, and further preferably, polyvinylidene fluoride can be cited. If the organic binder contains a fluoropolymer (polyvinylidene fluoride), excellent heat resistance and water resistance can be imparted to the carbon dioxide adsorption device.
[0078] The solubility of the organic binder in the protic polar solvent (typically water) is, for example, 0.1 g / 100 g-protic polar solvent or less, preferably 0.05 g / 100 g-protic polar solvent or less. If the solubility of the organic binder in the protic polar solvent (typically water) is below the above upper limit, excellent water resistance can be stably imparted to the acid gas adsorption device. It should be noted that the lower limit of the solubility of the organic binder in the protic polar solvent (typically water) is typically 0.01 g / 100 g-H2O or more.
[0079] The solubility parameter of the organic binder is, for example, 9 or more, preferably 10 or more, and is, for example, 15 or less, preferably 13 or less.
[0080] The carbon dioxide adsorbing layer may contain any appropriate additive material in addition to the carbon dioxide adsorbing particles and the organic binder.
[0081] The total content of the carbon dioxide adsorbing particles and the organic binder in the carbon dioxide adsorbing layer is, for example, 30% by volume or more, preferably 50% by volume or more, and is, for example, 100% by volume or less, preferably 99% by volume or less. It should be noted that the volume % can be measured, for example, by microstructural observation or elemental analysis.
[0082] The content of the carbon dioxide adsorbing particles in the carbon dioxide adsorption layer is, for example, 5% by volume or more, preferably 30% by volume or more. If the content of the carbon dioxide adsorbing particles is greater than the above lower limit, the carbon dioxide adsorption performance of the carbon dioxide adsorption device can be sufficiently ensured. The upper limit of the content of the carbon dioxide adsorbing particles is typically 85% by volume or less.
[0083] The content of the organic binder in the carbon dioxide adsorption layer is, for example, 5% by volume or more, preferably 15% by volume or more. If the content of the organic binder is greater than the above lower limit, the carbon dioxide adsorption particles can be prevented from falling off from the carbon dioxide adsorption layer in the adsorption step and / or the desorption step described later. The upper limit of the content of the organic binder is typically 70% by volume or less.
[0084] Typically, the carbon dioxide adsorption layer has interconnected pores. The carbon dioxide adsorption layer has a porosity of, for example, 10% to 90%, preferably 10% to 60%, and more preferably 15% to 40%.
[0085] Typically, a carbon dioxide adsorption layer comprising carbon dioxide adsorption particles and an organic binder is prepared by the following method. First, the organic binder is dissolved in an aprotic polar solvent to prepare a binder solution, the carbon dioxide adsorption particles are dispersed in the binder solution, and the binder solution is applied to the surface of a substrate to form a precursor film, and the aprotic polar solvent contained in the precursor film is replaced with a poor solvent for the organic binder to form a carbon dioxide adsorption layer. It should be noted that the method for forming the carbon dioxide adsorption layer is described in detail in the description of the reforming step in item E.
[0086] In addition, the method for preparing the carbon dioxide adsorption layer containing carbon dioxide adsorption particles and an organic binder is not limited to the above method. For example, the porous carrier may be dispersed in the binder solution, and the binder solution may be applied to the surface of the substrate to form a precursor film, and then the aprotic polar solvent contained in the precursor film may be replaced with a poor solvent for the organic binder to form a carrier-containing film containing a porous carrier and an organic binder, and then the carbon dioxide adsorbent may be supported on the porous carrier contained in the carrier-containing film to form a carbon dioxide adsorption layer.
[0087] Although not shown in the figure, the carbon dioxide adsorption device 100 can be equipped in a carbon dioxide adsorption device. In one embodiment, the carbon dioxide adsorption device includes: a plurality of carbon dioxide adsorption devices; a fan for supplying a gas containing CO2 (CO2-containing gas) to the carbon dioxide adsorption layer; and a pump for sucking CO2 desorbed from the carbon dioxide adsorption layer.
[0088] C. Adsorption process and separation process
[0089] As described above, the regeneration method of the carbon dioxide adsorbent according to one embodiment includes the following steps: an adsorption step in which CO 2 is adsorbed on the carbon dioxide adsorbent provided in the carbon dioxide adsorbent 100 ; and a desorption step in which CO 2 is desorbed from the carbon dioxide adsorbent.
[0090] In the adsorption process, typically, a CO2-containing gas is caused to flow through the gas flow path 16 so that CO2 contacts the carbon dioxide adsorption layer 15. The CO2-containing gas typically contains nitrogen in addition to CO2. In one embodiment, the CO2-containing gas is air (atmosphere). The CO2 concentration in the CO2-containing gas is, for example, greater than 100 ppm and less than 2% by volume. The temperature of the CO2-containing gas in the adsorption process is, for example, greater than 0°C and less than 40°C. The pressure of the CO2-containing gas in the adsorption process is, for example, 0.3×10 5 Pa or more and 2.0×10 5 Pa or less. The relative humidity RH of the CO2-containing gas in the adsorption process is, for example, 10% RH or more and 60% RH or less. The implementation time of the adsorption process is, for example, 15 minutes or more and 3 hours or less. The flow rate of the CO2-containing gas in the adsorption process is, for example, 0.5 m / sec or more and 5 m / sec or less.
[0091] Thus, the carbon dioxide adsorbent material facing the gas flow path 16 adsorbs CO2. The CO2 recovery rate in the adsorption process (=100-(CO2 concentration in the gas that has passed through the gas flow path / CO2 concentration in the gas before flowing into the gas flow path × 100)) is, for example, 80% or more, preferably 85% or more, more preferably 90% or more, and is, for example, 100% or less.
[0092] The separation process (sometimes also called the desorption process) is carried out after the adsorption process. In the separation process, typically, the carbon dioxide adsorption device is heated and the separated CO2 is sucked and recovered by a pump or the like, or the recovered CO2 is pumped into the carbon dioxide adsorption device again, heated, and the separated CO2 is recovered.
[0093] The temperature in the desorption step is, for example, higher than 40° C., preferably higher than 70° C., and is, for example, lower than 200° C., preferably lower than 110° C. The desorption step is performed for, for example, 1 minute to 1 hour.
[0094] As a result, CO 2 retained by the carbon dioxide adsorbent is released (released, desorbed) from the carbon dioxide adsorbent. Therefore, CO 2 can be recovered and utilized for various purposes (for example, metallization).
[0095] The above-mentioned adsorption step and desorption step are preferably repeated. In one embodiment, the adsorption step and desorption step are cyclically performed, for example, 10 times or more, preferably 30 times or more, more preferably 50 times or more, and further preferably 100 times or more.
[0096] D. Crushing process
[0097] In one embodiment, after the adsorption process and the desorption process are performed (preferably after the adsorption process and the desorption process are cycled within the above range), the crushing process is performed. In addition, the crushing process can be performed after the CO2 recovery rate in the adsorption process is less than the above lower limit.
[0098] In the crushing step, the carbon dioxide adsorption device 100 that has been subjected to the adsorption step and the desorption step is crushed. The carbon dioxide adsorption device can be crushed by any appropriate method according to the material of the substrate. Examples of the crushing method include a hammer mill, a roller mill, a jet mill, and a ball mill.
[0099] Thus, a recycled material powder is obtained. The recycled material powder contains components derived from the base material (eg, ceramic powder) and components derived from the carbon dioxide adsorbing layer (eg, carbon dioxide adsorbing material, porous carrier, organic binder).
[0100] The particle size of the recycled material powder is, for example, 0.1 μm or more, preferably 1.0 μm or more, and is, for example, 500 μm or less, preferably 50 μm or less. If the particle size of the recycled material powder is within the above range, the recycled material powder can be stably molded to obtain a substrate (honeycomb substrate).
[0101] E. Reforming process
[0102] In the reforming step, first, a binder, water or an organic solvent, a surfactant, a pH control agent, and a sintering aid are added to the recycled material powder obtained in the pulverizing step as needed, and kneaded to prepare a recycled blank or recycled slurry.
[0103] As the binder, for example, heat-curable thickening polysaccharides, methyl cellulose having thermal gelling properties, etc. can be cited, preferably, methyl cellulose can be cited. The binder can be used alone or in combination. The addition ratio of the binder is, for example, 0 mass parts or more, preferably 0.1 mass parts or more, and for example, 30 mass parts or less, preferably 10 mass parts or less, relative to 100 mass parts of the recycled material powder.
[0104] Next, if Figure 3As shown, the recycled material powder, recycled blank or recycled slurry is formed into a desired shape (representatively a honeycomb shape). The molding method can adopt any appropriate molding method. As the molding method, for example, extrusion molding, freeze molding, heating molding, pressure molding and spray drying method, fluidized bed granulation method can be cited, preferably, extrusion molding can be cited.
[0105] Thereafter, drying is performed as necessary, thereby producing a base material 1 (hereinafter referred to as a recycled base material 1R) composed of recycled material powder.
[0106] The regenerated base material 1R is preferably calcined after drying. This burns off combustible components (such as carbon dioxide adsorbent and binder) contained in the regenerated base material. As a result, fine pores are formed, and a high specific surface area can be expected.
[0107] The calcination temperature is, for example, 1200° C. or higher, preferably 1300° C. or higher, and, for example, 2200° C. or lower, preferably 1500° C. or lower. The calcination time is, for example, 1 hour or higher, preferably 2 hours or higher, and, for example, 100 hours or lower, preferably 20 hours or lower.
[0108] Next, a carbon dioxide adsorption layer 15 is newly formed on the surface of the produced regenerated substrate 1R (representatively, the partition wall 13). In the case of forming a carbon dioxide adsorption layer including a porous carrier, first, the porous carrier is added to a solvent and dispersed to prepare a dispersed slurry of the porous carrier. Examples of the solvent include water, alcohols, and glycols. The solvent can be used alone or in combination. Among the solvents, preferably, an aqueous solvent (water and a mixed solvent containing water) can be used.
[0109] The concentration of the porous carrier in the dispersed slurry is, for example, 10% by mass or more, preferably 15% by mass or more, and is, for example, 50% by mass or less, preferably 30% by mass or less. By adjusting the concentration of the porous carrier to the above range, a carbon dioxide adsorption layer can be stably formed on the regenerated substrate.
[0110] Next, a carbon dioxide adsorbent is added to the dispersed slurry liquid. The concentration of the carbon dioxide adsorbent in the dispersed slurry liquid is, for example, 5 mass % or more, preferably 10 mass % or more, and, for example, 30 mass % or less, preferably 20 mass % or less.
[0111] Next, a dispersion slurry containing a porous carrier and a carbon dioxide adsorbent is applied to the regenerated substrate 1R (specifically, the partition wall 13) by any appropriate method. In one embodiment, the dispersion is circulated in the cells 14 of the honeycomb substrate 10. Thus, the dispersion can be smoothly applied to the surface of the partition wall. The number of times the dispersion slurry is applied is appropriately changed according to the thickness of the carbon dioxide adsorption layer.
[0112] Next, the regenerated base material 1R coated with the dispersed slurry is heated to, for example, 50° C. to 200° C. to dry the coating, and sintered as needed. The drying time is, for example, 0.5 hours to 24 hours. In the case of sintering, the sintering is performed at, for example, 80° C. to 300° C. The sintering time is, for example, 1 hour to 100 hours.
[0113] Thus, a carbon dioxide adsorption layer including a porous carrier and a carbon dioxide adsorbent is formed on the regenerated base material 1R (specifically, the partition wall 13). It should be noted that when the carbon dioxide adsorption layer does not contain a porous carrier, the carbon dioxide adsorption layer can be formed on the regenerated base material 1R in the same manner as described above, except that the carbon dioxide adsorbent is added to the solvent without adding a porous carrier.
[0114] In another embodiment, for example, first, the above-mentioned dispersed slurry liquid is applied to the regenerated substrate 1R (specifically, the partition 13) in the same manner as described above. Next, after the coating on the regenerated substrate coated with the dispersed slurry liquid is dried, it is heated to, for example, 400° C. to 800° C. to be sintered. The sintering time is, for example, 1 hour to 100 hours. Thus, a carrier-containing membrane is formed. Next, for the carrier-containing membrane, a carbon dioxide adsorbent material that is liquid at room temperature and pressure, or a solution of the carbon dioxide adsorbent material is applied to the carrier-containing membrane in the same manner as described above. Thus, the carbon dioxide adsorbent material penetrates into and is carried on the porous carrier of the carrier-containing membrane. Thus, a carbon dioxide adsorption layer comprising a porous carrier and a carbon dioxide adsorbent material can also be formed on the regenerated substrate 1R.
[0115] In another embodiment, first, the organic binder is dissolved in an aprotic polar solvent to prepare a binder solution. The aprotic polar solvent can dissolve the organic binder but does not dissolve the carbon dioxide adsorbing particles (more specifically, the carbon dioxide adsorbing material).
[0116] As the aprotic polar solvent, any appropriate organic solvent may be used. Examples of the aprotic polar solvent include N-methyl-2-pyrrolidone (NMP), dimethylformamide (DMF), dimethylacetamide (DMA), dimethyl sulfoxide (DMSO), and tetrahydrofuran (THF). The aprotic polar solvent may be used alone or in combination.
[0117] Among the aprotic polar solvents, N-methyl-2-pyrrolidone (NMP) is preferably used. When the aprotic polar solvent contains NMP, the organic binder (particularly PVDF) can be dissolved more smoothly, and the dissolution of the carbon dioxide adsorbent can be stably suppressed.
[0118] The solubility parameter distance between the organic binder and the aprotic polar solvent is, for example, 3 or less, preferably 2 or less. If the solubility parameter distance between the organic binder and the aprotic polar solvent is below the above upper limit, the organic binder can be smoothly dissolved in the aprotic polar solvent. The lower limit of the solubility parameter distance between the organic binder and the aprotic polar solvent is typically 0 or more.
[0119] The solubility parameter distance between the carbon dioxide adsorbent and the aprotic polar solvent is, for example, 2 or more, preferably 3 or more, and more preferably 4 or more. If the solubility parameter distance between the carbon dioxide adsorbent and the aprotic polar solvent is greater than the above lower limit, the carbon dioxide adsorbent can be suppressed from dissolving in the aprotic polar solvent. The upper limit of the solubility parameter distance between the carbon dioxide adsorbent and the aprotic polar solvent is typically 10 or less.
[0120] Next, the carbon dioxide adsorbing particles are added to the binder solution and dispersed.
[0121] A solution in which an organic binder is dissolved in an aprotic polar solvent and particles having a carbon dioxide adsorbing capacity are dispersed (particle-dispersed binder solution) is applied to the surface of the regenerated base material 1R by any appropriate method in the same manner as described above.
[0122] Thus, the particle-dispersed binder solution is applied to the surface of the regenerated substrate (typically, the surface of the partition wall), thereby forming a precursor film. The precursor film includes the carbon dioxide adsorbing particles, the organic binder, and the aprotic polar solvent.
[0123] Next, the aprotic polar solvent contained in the precursor film is replaced with a poor solvent for the organic binder.
[0124] The poor solvent is less likely to dissolve the organic binder than the aprotic polar solvent (good solvent), and the organic binder is substantially insoluble in the poor solvent. Typically, the solubility parameter distance between the organic binder and the poor solvent is greater than the solubility parameter distance between the organic binder and the aprotic polar solvent (good solvent). The solubility parameter distance between the organic binder and the poor solvent is, for example, 2 or more, preferably 3 or more, and more preferably 4 or more.
[0125] Examples of the poor solvent include: protic polar solvents such as water, ethanol, butanol, isopropyl alcohol (IPA) and other alcohols; and freons such as hydrochlorofluorocarbons (HCFCs), hydrofluorocarbons (HFCs), and hydrofluoroolefins (HFOs). The poor solvent may be used alone or in combination. Among the poor solvents, water is preferably used.
[0126] By replacing the aprotic polar solvent, a membrane that is stable with respect to the protic solvent is obtained.
[0127] Thus, a carbon dioxide adsorption layer containing carbon dioxide adsorbing particles and an organic binder can be formed on the surface of the regenerated substrate (typically, the surface of the partition wall). Thereafter, the carbon dioxide adsorption layer is dried as necessary.
[0128] The method for forming the carbon dioxide adsorption layer including carbon dioxide adsorbing particles and an organic binder is not limited to the above embodiment. For example, first, a binder solution is prepared in the same manner as above. Next, the porous carrier is added to the binder solution and dispersed.
[0129] Thus, the porous carrier is dispersed in the binder solution, and a binder solution in which the porous carrier is dispersed (carrier-dispersed binder solution) is prepared.
[0130] Next, the carrier-dispersed binder solution is applied to the surface of the regenerated substrate using the above-mentioned coating method. Thus, the carrier-dispersed binder solution is applied to the surface of the regenerated substrate (representatively, the surface of the partition wall) to form a precursor film. The precursor film includes the above-mentioned porous carrier, the above-mentioned organic binder, and the above-mentioned aprotic polar solvent.
[0131] Next, the aprotic polar solvent contained in the precursor film is replaced with the above-mentioned poor solvent.
[0132] Thus, a carrier-containing film is formed on the surface of the regenerated substrate (typically, the surface of the partition wall). Thereafter, the carrier-containing film is dried as necessary. The carrier-containing film includes the porous carrier and the organic binder.
[0133] Next, the carbon dioxide adsorbent is supported on the porous carrier contained in the carrier-containing membrane. The carbon dioxide adsorbent used in this embodiment is preferably liquid at room temperature and pressure. More specifically, the carbon dioxide adsorbent that is liquid at room temperature and pressure is applied to the carrier-containing membrane using the above-mentioned coating method. As a result, the carbon dioxide adsorbent infiltrates and is supported on the porous carrier of the carrier-containing membrane, forming carbon dioxide adsorbent particles composed of the acidic gas adsorbent compound and the porous carrier. That is, the carbon dioxide adsorption layer is composed of carbon dioxide adsorbent particles and an organic binder.
[0134] In this way, the carbon dioxide adsorbing layer including the carbon dioxide adsorbing particles and the organic binder can be formed on the regenerated base material 1R.
[0135] In addition, the organic binder recovered from the recycled material powder can be used for the carbon dioxide adsorption layer. If the organic binder recovered from the recycled material powder is used, the manufacturing cost of the carbon dioxide adsorption device can be further reduced.
[0136] In the case where the carbon dioxide adsorption layer includes carbon dioxide adsorption-capable particles and an organic binder, the recycled material powder obtained by crushing the carbon dioxide adsorption device includes, for example, ceramic powder derived from the substrate, and carbon dioxide adsorption-capable particles and an organic binder derived from the carbon dioxide adsorption layer. In the case of recovering the organic binder from the recycled material powder, the recycled material powder is contacted with the above-mentioned aprotic polar solvent. Typically, the recycled material powder is added to the above-mentioned aprotic polar solvent and stirred. Thereby, the organic binder contained in the recycled material powder is dissolved in the aprotic polar solvent, and an organic binder solution is prepared. It should be noted that the ceramic powder and the carbon dioxide adsorption-capable particles are substantially insoluble in the aprotic polar solvent.
[0137] Next, the ceramic powder and the carbon dioxide adsorbing particles are preferably separated from the organic binder solution. Examples of the separation method include filtration.
[0138] Thereafter, the protic polar solvent (typically water) is added to the organic binder solution to precipitate the organic binder. Thus, the organic binder can be recovered and reused in the reforming step. That is, in the reforming step, an acidic gas adsorption layer containing the recovered organic binder and carbon dioxide adsorption particles can be formed on the surface of the regenerated substrate in the same manner as described above.
[0139] The organic binder recovered from the recycled material powder may contain carbon dioxide adsorbing particles (representatively inactivated carbon dioxide adsorbing particles) that cannot be separated from the organic binder solution by the above separation method and remain. If the organic binder containing a small amount of carbon dioxide adsorbing particles is used for the reformation of the acid gas adsorption layer, it can be combined with various materials (e.g., ceramic powder, porous carrier) contained in the recycled substrate. Therefore, the strength of the carbon dioxide adsorption device can be improved.
[0140] Through the above operations, Figure 1 The carbon dioxide adsorption device 100 shown is regenerated. In other words, the regeneration method of the above-mentioned carbon dioxide adsorption device (acidic gas adsorption device) is a method for manufacturing a carbon dioxide adsorption device (acidic gas adsorption device) having a carbon dioxide adsorption layer (acidic gas adsorption layer) whose performance has been restored. The method for manufacturing a carbon dioxide adsorption device (acidic gas adsorption device) includes: the above-mentioned adsorption step, the above-mentioned desorption step, the above-mentioned pulverization step, and the above-mentioned reforming step. In the method for manufacturing the above-mentioned carbon dioxide adsorption device (acidic gas adsorption device), a carbon dioxide adsorption device having excellent CO2 recovery performance (acidic gas recovery performance) can be manufactured. In addition, the regenerated carbon dioxide adsorption device (acidic gas adsorption device) can be subjected to the adsorption step and the desorption step in the same manner as described above, and then the pulverization step and the reforming step are again performed, thereby repeatedly regenerating.
[0141] Industrial Applicability
[0142] The acid gas adsorption device regeneration method according to the embodiment of the present invention can be used to regenerate an acid gas adsorption device used for separation and recovery of acid gas, and can be particularly preferably used to regenerate a carbon dioxide adsorption device used in a carbon dioxide recovery, utilization and storage (CCUS) cycle.
[0143] Explanation of symbols
[0144] 1. Substrate
[0145] 1R Recycled substrate
[0146] 10 Honeycomb substrate
[0147] 13 Next Door
[0148] 14 compartments
[0149] 15 Carbon dioxide adsorption layer
[0150] 100 Carbon dioxide adsorption device
Claims
1. A method for regenerating an acid gas adsorption device, comprising the following steps: supplying acid gas to the acid gas adsorption device so as to contact the acid gas adsorption layer of the acid gas adsorption device including a substrate and an acid gas adsorption layer, so that the acid gas is adsorbed on the acid gas adsorption material contained in the acid gas adsorption layer, wherein the acid gas adsorption layer is arranged on the surface of the substrate; allowing acid gas to be separated from the acid gas adsorbent material; crushing the acid gas adsorption device having carried out the step of adsorbing the acid gas and the step of releasing the acid gas to obtain a regeneration material powder; and The recycled material powder is molded into a substrate, and an acidic gas adsorbing layer containing an acidic gas adsorbing material is formed on the surface of the substrate.
2. The method for regenerating an acid gas adsorption device according to claim 1, wherein: The acid gas is carbon dioxide.
3. The method for regenerating an acid gas adsorption device according to claim 1, wherein: The substrate is a honeycomb substrate having partition walls defining a plurality of cells. The acid gas adsorption layer is formed on the surface of the partition wall.
4. The method for regenerating an acid gas adsorption device according to claim 1, wherein: The material constituting the substrate is selected from cordierite, alumina, mullite, silicon carbide, silicon-silicon carbide composite material, silicon nitride or a combination thereof.
5. The method for regenerating an acid gas adsorption device according to claim 1, wherein: The acidic gas adsorbent material is selected from nitrogen-containing compounds, organic metal structures, activated carbon, nitrogen-doped carbon, alkaline compounds, carbonates, bicarbonates, zeolites, ionic liquids or combinations thereof.
6. The method for regenerating an acid gas adsorption device according to claim 1, wherein: The acid gas adsorption layer further includes a porous carrier.
7. The method for regenerating an acid gas adsorption device according to claim 1, wherein: The acid gas adsorbing layer includes particles containing at least the acid gas adsorbing material and an organic binder capable of binding the particles. The organic binder is soluble in an aprotic polar solvent and substantially insoluble in a protic polar solvent.
8. The method for regenerating the acid gas adsorption device according to claim 7, further comprising the following steps: bringing an aprotic polar solvent into contact with the recycled material powder containing the organic binder, thereby dissolving the organic binder in the aprotic polar solvent; and adding a protic polar solvent to an organic binder solution obtained by dissolving the organic binder in an aprotic polar solvent to precipitate the organic binder, and recovering the organic binder; An acidic gas adsorbing layer including the recovered organic binder and particles containing at least the acidic gas adsorbing material is formed on the surface of a substrate obtained by molding the recycled material powder.
9. A method for manufacturing an acid gas adsorption device, comprising the following steps: supplying acid gas to the acid gas adsorption device so as to contact the acid gas adsorption layer of the acid gas adsorption device including a substrate and an acid gas adsorption layer, so that the acid gas is adsorbed on the acid gas adsorption material contained in the acid gas adsorption layer, wherein the acid gas adsorption layer is arranged on the surface of the substrate; allowing acid gas to separate from the acid gas adsorbent material; crushing the acid gas adsorption device having carried out the step of adsorbing the acid gas and the step of releasing the acid gas to obtain a regeneration material powder; and The recycled material powder is molded into a substrate, and an acidic gas adsorbing layer containing an acidic gas adsorbing material is formed on the surface of the substrate.
Citation Information
Patent Citations
Substrates for carbon dioxide capture and methods for making same
WO2013119929A1